2017
DOI: 10.1089/thy.2016.0426
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers Reflecting Thyroid Function in Athyreotic Patients on Levothyroxine Monotherapy

Abstract: Background: Some investigators reported that among athyreotic patients on levothyroxine (LT4) monotherapy following total thyroidectomy, the patients with normal serum thyrotropin (TSH) levels had mildly low serum free triiodothyronine (fT3) levels, whereas the patients with mildly suppressed serum TSH levels had normal serum fT3 levels, and the patients with strongly suppressed serum TSH had elevated serum fT3 levels. The objective of the present study was to clarify which of these three patient groups is clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 31 publications
(32 reference statements)
5
64
1
1
Order By: Relevance
“…17,18 After thyroidectomy, in the same patient treatment with levothyroxine (LT4) does not restore FT3 concentrations to the preoperative level at comparable TSH concentrations. 33,34 The impaired equilibria have been well recognised, being also associated with patient complaints during follow-up in LT4treated patients with thyroid carcinoma. 33,34 The impaired equilibria have been well recognised, being also associated with patient complaints during follow-up in LT4treated patients with thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 After thyroidectomy, in the same patient treatment with levothyroxine (LT4) does not restore FT3 concentrations to the preoperative level at comparable TSH concentrations. 33,34 The impaired equilibria have been well recognised, being also associated with patient complaints during follow-up in LT4treated patients with thyroid carcinoma. 33,34 The impaired equilibria have been well recognised, being also associated with patient complaints during follow-up in LT4treated patients with thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…32 Nor does it raise FT3 to levels observed in the healthy population when TSH returns into the reference range. 22,[33][34][35][36][37] Here, we explored the potential role of functional thyroid capacity in thyroid-pituitary regulation. 22,[33][34][35][36][37] Here, we explored the potential role of functional thyroid capacity in thyroid-pituitary regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sex hormone-binding globulin, cholesterol levels, and bone markers are generally considered to be relatively insensitive measures of thyroid status compared with TSH levels, a recent study comparing these measures in patients pre-thyroidectomy and post-thyroidectomy showed that these measures were best normalized in patients with mildly suppressed TSH values in the range of <0.03-≤0.3 mIU/L (17). If confirmed, this could suggest that TSH alone may not provide sufficient insight into thyroid status.…”
Section: Comparison Of Euthyroid Physiology With Physiology During Lementioning
confidence: 99%
“…5 Recently it has been shown that, in thyroidectomised patients, it is necessary to give suffi cient LT4 to achieve a low serum TSH if preoperative concentrations of serum T3 and thyroxine (T4) are to be restored. 6 National Health and Nutrition Examination Survey data have revealed that prescribing a dose of LT4 which restores serum TSH to its somewhat wide reference range is associated with lower serum T3 and lower T3:T4 ratios than euthyroid individuals not taking LT4. These biochemical disadvantages were associated with adverse objective and subjective parameters, such as increased body mass index, lipid profi le and feelings of poor health.…”
mentioning
confidence: 99%